2017
DOI: 10.1186/s12903-017-0352-y
|View full text |Cite
|
Sign up to set email alerts
|

Dental anomalies: prevalence and associations between them in a large sample of non-orthodontic subjects, a cross-sectional study

Abstract: BackgroundTo analyze the prevalence and associations between dental anomalies detectable on panoramic radiographs in a sample of non-orthodontic growing subjects.MethodsFor this cross-sectional study, digital panoramic radiographs of 5005 subjects were initially screened from a single radiographic center in Rome. Inclusion criteria were: subjects who were aged 8–12 years, Caucasian, and had good diagnostic quality radiographs. Syndromic subjects, those with craniofacial malformation, or orthodontic patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
123
7
25

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 24 publications
18
123
7
25
Order By: Relevance
“…Thus, these teeth are frequently affected by agenesis (4.28-7.52%) which is in accordance with our results [4][5][6][7]18]. A rare occurrence of oligodontia was reported in the Italian population (0.08%) which is in agreement with our result (0.09%) [24]. Contrary to the high prevalence of hypodontia, supernumerary teeth are less frequently found in healthy individuals (0.5-3.8%).…”
Section: Abnormalities Of Tooth Numbersupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, these teeth are frequently affected by agenesis (4.28-7.52%) which is in accordance with our results [4][5][6][7]18]. A rare occurrence of oligodontia was reported in the Italian population (0.08%) which is in agreement with our result (0.09%) [24]. Contrary to the high prevalence of hypodontia, supernumerary teeth are less frequently found in healthy individuals (0.5-3.8%).…”
Section: Abnormalities Of Tooth Numbersupporting
confidence: 92%
“…Contrary to the high prevalence of hypodontia, supernumerary teeth are less frequently found in healthy individuals (0.5-3.8%). The prevalence of supernumerary teeth in our sample was 4.4%, slightly higher than in recent studies [24,25,26]. The etiological pattern of sex distribution in association with supernumerary teeth is the opposite of hypodontia [1].…”
Section: Abnormalities Of Tooth Numbercontrasting
confidence: 72%
“…Another finding in the present study was tooth retention or impaction (third molars excluded) in 17% (2/12). A study by Lagana et al [21] reported an impaction prevalence of 3.9% in a group of 4706 aged 8−12-years. Retention of permanent second molars is a frequent finding in OI [5, 6, 22], but was not found in any individuals in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dental ankylosis has been reported to range from 2% to 5% depending on the population and type of dentition . Despite the relatively low reported prevalence, dental ankylosis can significantly affect esthetics and function when it occurs in a tooth that is not fully erupted.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The prevalence of dental ankylosis has been reported to range from 2% to 5% depending on the population and type of dentition. [6][7][8][9] Despite the relatively low reported prevalence, dental ankylosis can significantly affect esthetics and function when it occurs in a tooth that is not fully erupted. Successful management of dentoalveolar ankylosis in the esthetic zone often demands a multidisciplinary approach including orthodontics, periodontics, endodontics, and a full range of restorative options from conservative adhesive strategies to dentoalveolar surgery and implant-supported restorations.…”
Section: Introductionmentioning
confidence: 99%